Penggunaan Limbah Kertas sebagai Bahan Pembuatan Brickwall untuk Meningkatkan Pendapatan Produsen Bata di Kota Pagar Alam - Dhiniati, Fameira; Aminah, Siti; Aisah, Elpita (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Paper waste found in Pagar Alam City is an inorganic waste that is no longer used and is difficult to decompose. Inorganic waste that is not utilized can cause soil pollution, which can damage the condition of the soil. Currently, the handling of paper waste is still less than optimal, therefore it is necessary to apply the 3-R principle (Reduce, Reuse, Recycle). One activity to reduce paper waste is to use paper waste as material for making brickwalls. The aim of this activity is to empower and motivate brick producers to use paper waste as an innovation for making brickwalls. Method: The stages of service activities start from the stage of education on paper waste, carrying out brickwall making, installation techniques and sales techniques. The methods in this service include: Socialization regarding the use of waste paper, analysis of business feasibility and problems of brick producers, Training on the application of waste paper for brickwall and business management, Practice of brickwall installation techniques, Training on marketing or sales techniques and, Program evaluation, and Sustainability of the program service is through mentoring and continuing activities through PPPM as Real Work Lectures and Assisted Village activities. Results: The result of this PKM activity is to produce brickwall products using paper waste which have greater selling value for brick producers in Pagaralam City. Conclusion: The level of sales increased with assistance in creating social media and production on the producer's side increased.